Teacher Social and Personality Development Model Based on Myers Briggs Type Indicator - Supadi (Journal of Education Reseach and Evaluation, 2022)
Developing teacher social competence is a series of activities to improve teaching staff quality. The Myers-Briggs Type Indicator (MBTI) is a psychological test designed to measure a person's basic psychological preferences for seeing the world and making decisions. The purpose of this study was to develop a Model of Teacher Personality and Social Competence Development Based on the Myers-Briggs Type Indicator (MBTI). The method used is research and development procedures. The total number of respondents obtained was 51 people. The research instrument used is a questionnaire developed by the researcher. In order to test the practicality and effectiveness of the self-development model conducted a broader product test, revision of the results of a more comprehensive field test, a large-scale feasibility test, and final revision of the results of the feasibility test. The results of the analysis of the needs for social competence and personality of teachers based on MBTI consist of a series of training to produce quality teachers, including personal grooming, multicultural learning, interpersonal skills, team building, and public speaking according to the personality type of each teacher. Most teachers in this study have a strong personality and social competence. When viewed from the personality type, it can be said that teachers with extrovert traits' personality and social competence tend to be high. In contrast, teachers with introverted traits tend to have low personality and social competencies. Teachers with intuitive and sensing traits tend to have strong personalities and social competence.